The 14th five-year plan of the People Republic of China fostering high quality development. (Observations and suggestions., 2021)
They focus on innovation driven growth, low carbon development, integration of urban rural areas with deeper social inclusion, and population aging. The 14th Five Year Plan highlights high quality green development and emphasizes innovation as the core of modern development, relying on the dual circulation strategy as the growth paradigm coupled with reforms to increase living standards. Building on the achievements of the 13th Plan, it aims to reduce the carbon intensity of the economy and peak carbon dioxide emissions before 2030.